Islamic financial inclusion and human development nexus: Evidence from Sumatra Island, Indonesia - Ruslan Husein Marasabessy; Evan Hamzah Muchtar (Faculty of Islamic Economics and Business, UIN Salatiga, 2025)
Sumatra Island is one of the main targets in the development of Islamic economics and finance. This development is expected to bring significant impacts on socio-economy. Therefore, this study aims to examine the relationship between Islamic financial inclusion and human development index (HDI) in Sumatra Island, Indonesia. The study procedures were carried out using panel data on Islamic financial inclusion from 10 provinces from 2015 - 2022. Data was then analyzed using regression analysis and processed with Stata software. The results showed that there was a positive and significant relationship between financial inclusion index and HDI. To provide a broader impact on human development, it was necessary to increase Islamic financial inclusion in Sumatra Island. Therefore, bank managers must provide access to the unbanked community by opening wider and easier banking services for the unbanked. This study also provided recommendations for strategies to accelerate formal Islamic financial inclusion in Sumatra Island.